2019
DOI: 10.1519/jsc.0000000000002133
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feedback Attenuates Mean Concentric Barbell Velocity Loss and Improves Motivation, Competitiveness, and Perceived Workload in Male Adolescent Athletes

Abstract: It is unknown whether instantaneous visual feedback of resistance training outcomes can enhance barbell velocity in younger athletes. Therefore, the purpose of this study was to quantify the effects of visual feedback on mean concentric barbell velocity in the back squat, and to identify changes in motivation, competitiveness, and perceived workload. In a randomised-crossover design (Feedback vs. Control) feedback of mean concentric barbell velocity was or was not provided throughout a set of 10 repetitions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 31 publications
5
107
0
5
Order By: Relevance
“…Muscular strength and power are key attributes of RU performance due to the contact and collision element of the sport [75]. Six studies have presented strength and power data in age-grade RU players via Wattbike peak power output [64], countermovement jump [46,62] or isoinertial strength tests [46,62,[65][66][67]. Strength and power are greater in older age categories [62,64] supporting data in rugby league [53,68].…”
Section: Muscular Strength and Powermentioning
confidence: 88%
See 1 more Smart Citation
“…Muscular strength and power are key attributes of RU performance due to the contact and collision element of the sport [75]. Six studies have presented strength and power data in age-grade RU players via Wattbike peak power output [64], countermovement jump [46,62] or isoinertial strength tests [46,62,[65][66][67]. Strength and power are greater in older age categories [62,64] supporting data in rugby league [53,68].…”
Section: Muscular Strength and Powermentioning
confidence: 88%
“…Previous research has presented the physical qualities of senior [53][54][55][56] and youth [53,[57][58][59] RU players across multiple ages, standards and positions. Specific to male age-grade RU players within England, ten studies [46,49,[60][61][62][63][64][65][66][67] have presented data across various physical qualities making comparisons between age, position and playing level. Tables 4 and 5 present the physical qualities for age-grade RU players from England and provide objective markers of physical development to support talent identification and development [68].…”
Section: Physical Qualitiesmentioning
confidence: 99%
“…Both groups received the same encouragement to lift with maximal intended concentric velocity and complete the eccentric phase in a controlled manner, although neither group received instantaneous velocity information to control for the effect of feedback. 18 Following back squats, participants then completed the same four supplementary exercises (Nordic lower/Romanian deadlift, upper-body push, upper-body pull, anti-extension) using body weight or a repetitions in reserve approach to adjust load (Table 1).…”
Section: Training Routinementioning
confidence: 99%
“…8 The use of augmented feedback has been well established as a method of promoting acute performance enhancement and mitigating the effects of fatigue during exercise. [9][10][11][12] For example, during resistance training it has been demonstrated that providing barbell velocity visually when exercising can enhance barbell speed by 7.7% compared to athletes who do not receive this feedback. 11 Furthermore, running performance and perceptions of effort can be improved when frequent positive encouragement is provided to athletes in maximal exercise tests.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] For example, during resistance training it has been demonstrated that providing barbell velocity visually when exercising can enhance barbell speed by 7.7% compared to athletes who do not receive this feedback. 11 Furthermore, running performance and perceptions of effort can be improved when frequent positive encouragement is provided to athletes in maximal exercise tests. 12 It is thought that these improvements in physical performance are due to externalised focus which can mitigate feelings of fatigue 12 and improve motivation and competitiveness.…”
Section: Introductionmentioning
confidence: 99%